Preparation method of amorphous oxide coated and modified lithium ion positive electrode material and lithium ion battery

By uniformly covering silicate high-entropy amorphous materials on the surface of the positive electrode material of lithium-ion batteries, the problem of material instability in traditional lithium-ion batteries at high voltage is solved, the electrochemical performance and cycle life are improved, and the preparation is reduced cost.

CN119230789APending Publication Date: 2024-12-31UNIV OF ELECTRONICS SCI & TECH OF CHINA

Patent Information

Application Number
CN202411501523.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The oxidation state of the positive electrode material increases at high voltages, resulting in unstable nickel redox reaction, structural denaturation, decreased conductivity, electrolyte decomposition to produce poor by-products, affecting the structural and electrochemical performance of the battery, and existing The coating method has problems with excessive local acidity or dissolution of lithium elements.

Method used

Silicate high-entropy amorphous materials are uniformly coated on the surface of the positive electrode material by hydrothermal method and mechanical ball milling method to form an amorphous oxide layer, which improves structural stability and conductivity, and reduces harmful phase change at high voltage and Delivery grain boundary dislocation.

Benefits of technology

The positive electrode material is realized to work stably under high voltage, improve electrochemical performance and cycle life, reduce preparation costs, avoid thermal runaway at high voltage, and enhance the safety and conductivity of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230789A_ABST
    Figure CN119230789A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of an amorphous oxide coated and modified lithium ion positive electrode material and a lithium ion battery. According to the preparation method disclosed by the invention, the silicate high-entropy amorphous material is selected as a modification raw material, the advantage that the bulk phase Young modulus of the amorphous material is low by several orders of magnitude is utilized, and the amorphous material is uniformly coated on the surface of the positive electrode material in a simple mechanical mixing and heat treatment matching manner, so that the modification of the positive electrode material is realized; the positive electrode material can stably work under high voltage; and the preparation method can realize uniform coating of the surface without using a solution environment, so that the synthesis cost of the modified lithium cobalt oxide is effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a method for preparing a lithium ion positive electrode material coated and modified by an amorphous oxide, and a lithium ion battery. Background Art

[0002] With the increasing demand for electric vehicles, renewable energy storage and portable electronic devices, traditional lithium-ion batteries have been unable to meet the requirements of high energy density. Therefore, the development of high-voltage positive electrode materials to improve the energy density of batteries has become an important research direction. Lithium cobalt oxide, high nickel ternary, lithium-rich manganese-based and other positive electrode materials are the mainstream positive electrode materials widely used in the market. By increasing the cut-off voltage, the battery capacity density and energy density can be effectively improved, but when the voltage reaches a critical voltage, the positive electrode material will fail irreversibly. This is mainly because high voltage brings the following problems: 1) Under high voltage, the oxidation state of the positive electrode material increases, resulting in unstable redox reaction of nickel and release of oxygen, which affects the structural stability and electrochemical performance of the material; 2) High nickel positive electrode is prone to phase change under high voltage, such as from layered structure to spinel structure, resulting in reduced ion migration rate and decreased conductivity; 3) High voltage will accelerate the decomposition of electrolyte and generate undesirable by-products. These by-products may be deposited on the electrode surface to form a passivation layer, reducing ion conductivity; 4) Under high voltage, lithium ions may escape from high nickel positive electrode materials, resulting in delithiation of the material, which in turn affects the overall structure and electrochemical performance of the material; 5) High voltage operation will cause the thermal stability of the material to decrease, which will in turn cause thermal runaway or thermal collapse, affecting battery safety and cycle life.

[0003] In order to improve the interface stability and maintain the electrochemical performance, researchers have explored a variety of modification strategies. Taking LiCoO2 (LCO) positive electrode material as an example, coating it has been proven to effectively protect LCO from electrolyte erosion, while inhibiting harmful phase changes under high voltage, thereby improving interface stability and material performance. Patent CN109037639A discloses a preparation method for a nickel-doped lithium manganese oxide composite material, but the aluminum nitrate solution used in this method is a strong acidic solution. Direct addition will cause excessive local acidity, causing the dissolution of nickel and manganese elements on the surface of the lithium cobalt oxide material, affecting the stability and safety of the material. Patent CN103794776B discloses a coating method for lithium cobalt oxide materials for lithium-ion batteries, proposing to use aqueous solutions and soluble salts to coat the surface of lithium cobalt oxide materials, but this method will cause the lithium element on the surface of the particles to dissolve, resulting in chemical element vacancies and affecting the electrochemical properties of the material.

[0004] Amorphous materials have many physical, chemical and electromagnetic properties that are superior to crystalline materials due to their short-range order, long-range disorder and isotropy. How to combine amorphous materials to coat and modify lithium cobalt oxide positive electrode materials and improve the stability of positive electrode materials when working at high voltage has become a key focus. Summary of the invention

[0005] In view of the problems existing in the background technology, the purpose of the present invention is to provide a preparation method and a lithium-ion positive electrode material coated with an amorphous oxide and modified. The preparation method of the present invention selects a silicate high-entropy amorphous material as a modified raw material, takes advantage of the fact that the bulk Young's modulus of the amorphous material is several orders of magnitude lower, and adopts a simple mechanical mixing and heat treatment method to uniformly coat the amorphous material on the surface of the positive electrode material, thereby achieving the modification of the positive electrode material, so that the positive electrode material can work stably under high pressure; and the preparation method can achieve uniform surface coating without using a solution environment, effectively reducing the synthesis cost of modified lithium cobalt oxide.

[0006] To achieve the above object, the technical solution of the present invention is as follows:

[0007] A method for preparing an amorphous oxide-coated modified lithium-ion positive electrode material comprises the following steps:

[0008] Step 1. Weigh sodium salt, potassium salt, silicon salt, aluminum salt and M metal salt according to the molar ratio of the elements, and prepare a silicate high entropy amorphous material by a hydrothermal method;

[0009] Step 2. The silicate high entropy amorphous material obtained in step 1 and the conventional positive electrode material are mixed in a certain mass ratio, and the mixed powder is ball-milled by mechanical ball milling to make the mixture uniform;

[0010] Step 3. Place the material obtained by mixing in step 2 in a heating furnace and sinter it in an air atmosphere. After sintering, cool it naturally to obtain the desired lithium-ion positive electrode material.

[0011] Furthermore, the conventional positive electrode material is a lithium cobalt oxide positive electrode material, a lithium-rich manganese-based positive electrode material or a high-nickel ternary positive electrode material.

[0012] Furthermore, in step 1, the sodium salt is preferably sodium hydroxide, sodium nitrate, sodium sulfate or sodium acetate, the potassium salt is preferably potassium hydroxide, potassium nitrate, potassium sulfate or sodium potassium acetate, the silicon salt is preferably silicon tetrachloride, and the aluminum salt is preferably aluminum nitrate, aluminum sulfate, aluminum acetate; the M metal salt is preferably M nitrate, M sulfate, M acetate, M oxalate or ammonium salt.

[0013] Furthermore, the specific process of the hydrothermal method is:

[0014] Step 1.1: Place all the weighed substances in a solvent and stir to fully dissolve them to obtain solution A;

[0015] Step 1.2: Add an aqueous ammonia solution to solution A and adjust the pH value to 10-12 to obtain solution B;

[0016] Step 1.3: placing solution B in a hydrothermal kettle for hydrothermal reaction, cooling naturally to room temperature after the reaction is completed, then pouring out the supernatant in the hydrothermal kettle, taking out the precipitate in the hydrothermal kettle, and then washing the precipitate to obtain a solid precursor material;

[0017] Step 1.4: Sinter the solid precursor material obtained in step 1.3 in an air atmosphere, and naturally cool to room temperature after sintering to obtain the desired silicate high entropy amorphous material.

[0018] Furthermore, the structural formula of the silicate high entropy amorphous material is (Na x K 1-x )(Al y M 1-y )Si3O 8±δ , wherein M is a combination of four metal elements, and the molar ratio of the four elements is approximately, preferably equal; the four metal elements are any four of Mg, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, In, La, and Ce; wherein 0 <x<1,0.5≤y≤0.6,0<δ<1。

[0019] Furthermore, in step 2, the mass ratio of the silicate high entropy amorphous material to the conventional positive electrode material is 0.1% to 10%:1.

[0020] Furthermore, in step 2, the ball milling mixing time ranges from 1 to 8 hours, and the ball milling mixing speed ranges from 300 to 1000 rpm.

[0021] Furthermore, in step 3, the sintering temperature is 400-800° C. and the sintering time is 2-6 hours.

[0022] The present invention provides a lithium ion battery prepared based on the above-mentioned amorphous oxide-coated lithium cobalt oxide material, wherein the lithium ion battery comprises an amorphous oxide-coated modified lithium ion positive electrode, a lithium negative electrode and an electrolyte.

[0023] The present invention also provides a method for preparing the above lithium ion battery, comprising the following steps:

[0024] Step S1. Mixing the amorphous oxide-coated positive electrode material with conductive graphite, PVDF binder, and N-methylpyrrolidone (NMP) in a certain mass ratio;

[0025] Step S2. After mixing, all the raw materials are uniformly mixed by mechanical homogenization, and the homogenization time ranges from 60 to 120 minutes;

[0026] Step S3. coating the mixed slurry on the copper foil with a coating thickness of 50-150 μm;

[0027] Step S4. Bake the coated copper foil at a certain temperature for 6 to 12 hours to remove the NMP solvent;

[0028] Step S5. Place the dried electrode obtained in step 4 in a vacuum oven and bake for 6 to 12 hours to remove moisture adsorbed by the electrode;

[0029] Step S6. After obtaining the electrode sheet, cut it into positive electrode sheets of a certain diameter;

[0030] Step S7. Assemble the positive electrode sheet, electrolyte and metal lithium sheet to obtain the desired lithium-ion battery.

[0031] The mechanism of the present invention is: coating the surface of conventional positive electrode materials with an amorphous oxide layer improves their structural stability, inhibits harmful phase changes of materials under high voltage, reduces grain boundary dislocations and internal stresses in high-delithiation states, and further reduces the charge transfer impedance at the interface between the positive electrode material and the electrolyte, thereby facilitating the electrochemical stability of lithium cobalt oxide materials for lithium-ion batteries, and solving the problems of circulation, storage, and floating charge faced by the development of high-voltage materials. At the same time, the amorphous oxide nanolayer has a good lithium ion transmission rate, and the Na and K alkali metal elements in the amorphous oxide are doped into the Li ion site, which improves the conductivity and capacity density of conventional positive electrode materials; the metal elements such as Al and M are doped into the transition metal ion site, which expands the ion framework of conventional positive electrode materials, making it easier for lithium ions to migrate, so that the conventional positive electrode materials coated with amorphous nanolayers have excellent electrical properties.

[0032] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0033] The present invention adopts a simple mechanical ball milling and hydrothermal precipitation method to coat and modify conventional positive electrode materials, and uniformly grows a dense amorphous oxide protective film on the surface of conventional positive electrode materials. Compared with the currently commonly used ball milling method, vapor deposition method and other methods, the method of the present invention is simple and has low preparation cost. At the same time, since the amorphous material has a low bulk Young's modulus and good shape retention, it can be uniformly coated on the surface of conventional positive electrode materials; compared with the prior art method of using cobaltous hydroxide for surface modification to eliminate residual lithium on the surface, the method of the present invention can achieve the effect of modifying the surface while also playing the role of surface modification to improve material performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1This is the SEM of the silicate amorphous oxide nanomaterial prepared by the hydrothermal method in Example 1.

[0035] Figure 2 TEM of the modified lithium cobalt oxide material prepared in Example 1 and Comparative Example 1.

[0036] Figure 3 It is a cycle comparison data chart of lithium ion batteries obtained based on Examples 1 to 5 and unmodified lithium cobalt oxide positive electrode materials.

[0037] Figure 4 This is a cycle comparison data chart of a lithium-ion battery obtained based on Example 6 and an unmodified lithium-rich manganese-based positive electrode material.

[0038] Figure 5 This is a cycle comparison data chart of lithium-ion batteries obtained based on Example 7 and unmodified high-nickel ternary positive electrode materials. DETAILED DESCRIPTION

[0039] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with the implementation modes and the accompanying drawings.

[0040] Example 1

[0041] A method for preparing a lithium ion cobalt oxide positive electrode material coated and modified by an amorphous oxide comprises the following steps:

[0042] Step 1. Sodium hydroxide, potassium nitrate, silicon tetrachloride, aluminum sulfate, chromium nitrate, manganese nitrate, iron nitrate and cobalt nitrate were weighed according to the molar ratio of elements Na:K:Si:Al:Cr:Mn:Fe:Co=0.5:0.5:3:0.6:0.1:0.1:0.1, and then a hydrothermal method was used to prepare a molten salt of (Na 0.5 K 0.5 )(Al 0.6 Cr 0.1 Mn 0.1 Fe 0.1 Co 0.1 )Si3O 8±δ The silicate high entropy amorphous material, the specific process is:

[0043] Step 1.1: Place all the weighed substances in pure water and stir for 60 minutes to fully dissolve them to obtain solution A;

[0044] Step 1.2: Add an aqueous ammonia solution to solution A and adjust the pH value to 10 to obtain solution B;

[0045] Step 1.3: Place solution B in a hydrothermal kettle for hydrothermal reaction at a reaction temperature of 180°C for 12 hours; after the reaction is completed, cool naturally to room temperature, pour out the supernatant in the hydrothermal kettle, take out the precipitate in the hydrothermal kettle, and then wash the precipitate to obtain a solid precursor material;

[0046] Step 1.4: Sinter the obtained solid precursor material in an air atmosphere at a sintering temperature of 700°C and a sintering time of 12 hours. After sintering, cool it naturally to room temperature and use a sieve to screen to obtain a silicate high entropy amorphous material of the desired target size.

[0047] Step 2. The silicate high entropy amorphous material obtained in step 1 and lithium cobalt oxide are mixed in a mass ratio of 0.03:1, and the mixed powder is ball-milled by mechanical ball milling. The ball milling mixing time is 4 hours and the ball milling mixing speed is 500 rpm to make the mixture uniform;

[0048] Step 3. Place the material mixed evenly in step 2 into a heating furnace and sinter it in an air atmosphere at a sintering temperature of 450°C and a sintering time of 3 hours. After sintering, cool naturally to obtain the desired lithium cobalt oxide positive electrode material.

[0049] Example 2

[0050] The lithium cobalt oxide positive electrode material was prepared according to the steps of Example 1, except that the mass ratio of the silicate high entropy amorphous material to the lithium cobalt oxide in step 2 was adjusted to 0.01:1, and the other steps remained unchanged.

[0051] Example 3

[0052] The lithium cobalt oxide positive electrode material was prepared according to the steps of Example 1, except that the mass ratio of the silicate high entropy amorphous material to the lithium cobalt oxide in step 2 was adjusted to 0.05:1, and the other steps remained unchanged.

[0053] Example 4

[0054] The lithium cobalt oxide positive electrode material was prepared according to the steps of Example 1, except that the structural formula of the silicate high entropy amorphous material in step 1 was adjusted to (Na 0.3 K 0.7 )(Al 0.5 Ca 0.1 Mg 0.1 Fe 0.2 Ti 0.1 )Si3O 8±δ , the other steps remain unchanged.

[0055] Example 5

[0056] The lithium cobalt oxide positive electrode material was prepared according to the steps of Example 1, except that the structural formula of the silicate high entropy amorphous material in step 1 was adjusted to (Na0.6 K 0.4 )(Al 0.6 Cr 0.1 Mn 0.1 Zn 0.1 Cu 0.1 )Si3O 8±δ , the other steps remain unchanged.

[0057] Example 6

[0058] The lithium-rich manganese-based positive electrode material was prepared according to the steps of Example 4, except that the lithium cobalt oxide in step 2 was adjusted to a lithium-rich manganese-based material, and the other steps remained unchanged.

[0059] Example 7

[0060] A high-nickel ternary positive electrode material was prepared according to the steps of Example 5, except that the lithium cobalt oxide in step 2 was adjusted to a high-nickel ternary material, and the other steps remained unchanged.

[0061] Comparative Example 1

[0062] The lithium cobalt oxide positive electrode material was prepared according to the steps of Example 1, except that the sintering temperature in step 3 was adjusted to 900° C. or the sintering time was adjusted to 8 h, and the other steps remained unchanged.

[0063] A lithium-ion battery is prepared based on the positive electrode material prepared in the embodiment and the conventional lithium cobalt oxide positive electrode material without modification, the lithium-rich manganese-based positive electrode material and the high-nickel ternary positive electrode material, and the preparation method thereof comprises the following steps:

[0064] Step S1. Mixing the positive electrode material prepared in the embodiment and the comparative example with conductive graphite, PVDF binder, and N-methylpyrrolidone (NMP) in a certain mass ratio;

[0065] Step S2. After mixing, all the raw materials are mixed evenly by mechanical homogenization, and the homogenization time range is 120min;

[0066] Step S3. coating the mixed slurry on the copper foil with a coating thickness of 100 μm;

[0067] Step S4. Bake the coated copper foil at a certain temperature for 12 hours to remove the NMP solvent;

[0068] Step S5. Place the dried electrode obtained in step 4 in a vacuum oven and bake for 12 hours to remove moisture adsorbed by the electrode;

[0069] Step S6. After obtaining the electrode sheet, cut it into positive electrode sheets of a certain diameter;

[0070] Step S7. Assemble the positive electrode sheet, electrolyte and metal lithium sheet to obtain the desired button-type lithium-ion battery.

[0071] Electrochemical testing of button-type lithium-ion batteries: Half cells are used to test the electrochemical properties of the prepared materials.

[0072] The cyclic charge and discharge test was carried out between 3V and 4.55V, with 3 activation cycles and an activation current density of 0.1C; 100 cycles and a cyclic current density of 0.5C (1C = 200mAh / g). The charge and discharge test results are shown in Table 2.

[0073] Note: The voltage range of lithium-rich manganese-based positive electrode materials is 2.1~4.8V, 1C=250mAh / g; the voltage range of high-nickel ternary positive electrode materials is 2.8~4.3V, 1C=200mAh / g.

[0074] Table 2 Comparison of electrochemical performance results between the embodiment and pure lithium cobalt oxide

[0075]

[0076] Figure 1 This is a SEM of the silicate amorphous oxide nanomaterial prepared by the hydrothermal method in Example 1. As can be seen from the figure, the amorphous oxide prepared by the hydrothermal method can reach the nanometer level, which is conducive to the subsequent uniform coating of conventional positive electrode materials.

[0077] Figure 2 This is the TEM of the modified lithium cobalt oxide material prepared in Example 1, Comparative Example 1. From the figure, it can be seen that if the sintering temperature is too high or the sintering time is too long, the amorphous material coated on the surface of the lithium cobalt oxide material will be partially or completely converted into a single crystal material.

[0078] Figure 3 This is a cycle comparison data diagram of lithium-ion batteries obtained based on Examples 1 to 5 and unmodified lithium cobalt oxide positive electrode materials; Figure 4 This is a cycle comparison data diagram of a lithium-ion battery obtained based on Example 6 and an unmodified lithium-rich manganese-based positive electrode material; Figure 5 This is a cycle comparison data chart of lithium-ion batteries obtained based on Example 7 and unmodified high-nickel ternary positive electrode materials.

[0079] Combining Table 2 and Figures 3 to 5 It can be seen that the positive electrode material coated with the amorphous oxide nanolayer has more stable electrochemical performance, higher initial capacity and coulombic efficiency, and longer cycle performance; and has obvious advantages over the unmodified pure positive electrode material.

[0080] The above description is only a specific implementation mode of the present invention. Any feature disclosed in this specification, unless otherwise stated, can be replaced by other alternative features that are equivalent or have similar purposes; all the disclosed features, or all the steps in the methods or processes, except for mutually exclusive features and / or steps, can be combined in any way.

Claims

1. A method for preparing a lithium-ion positive electrode material coated and modified by an amorphous oxide, characterized in that: The following steps are involved: Step 1. Weigh sodium salt, potassium salt, silicon salt, aluminum salt and M metal salt according to the molar ratio of the elements, and prepare a silicate high entropy amorphous material by a hydrothermal method; Step 2. The silicate high entropy amorphous material obtained in step 1 and the conventional positive electrode material are mixed in a certain mass ratio, and the mixed powder is ball-milled by mechanical ball milling to make the mixture uniform; Step 3. Place the material obtained by mixing in step 2 in a heating furnace and sinter it in an air atmosphere. After sintering, cool it naturally to obtain the desired lithium-ion positive electrode material.

2. The method for preparing a lithium ion positive electrode material according to claim 1, characterized in that: The conventional positive electrode material is a lithium cobalt oxide positive electrode material, a lithium-rich manganese-based positive electrode material or a high-nickel ternary positive electrode material.

3. The method for preparing a lithium ion positive electrode material according to claim 1, characterized in that: In step 1, the sodium salt is sodium hydroxide, sodium nitrate, sodium sulfate or sodium acetate, the potassium salt is potassium hydroxide, potassium nitrate, potassium sulfate or sodium potassium acetate, the silicon salt is silicon tetrachloride, and the aluminum salt is preferably aluminum nitrate, aluminum sulfate, aluminum acetate; the M metal salt is M nitrate, M sulfate, M acetate, M oxalate or ammonium salt.

4. The method for preparing a lithium ion positive electrode material according to claim 1, characterized in that: The specific process of the hydrothermal method is: Step 1.1: Place all the weighed substances in a solvent and stir to fully dissolve them to obtain solution A; Step 1.2: Add an aqueous ammonia solution to solution A and adjust the pH value to 10-12 to obtain solution B; Step 1.3: placing solution B in a hydrothermal kettle for hydrothermal reaction, cooling naturally to room temperature after the reaction is completed, then pouring out the supernatant in the hydrothermal kettle, taking out the precipitate in the hydrothermal kettle, and then washing the precipitate to obtain a solid precursor material; Step 1.4: Sinter the solid precursor material obtained in step 1.3 in an air atmosphere, and naturally cool to room temperature after sintering to obtain the desired silicate high entropy amorphous material.

5. The method for preparing a lithium ion positive electrode material according to claim 4, characterized in that: The structural formula of the silicate high entropy amorphous material is (Na x K 1-x )(Al y M 1-y )Si3O 8±δ , wherein M is a combination of four metal elements; the four metal elements are any four of Mg, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, In, La, and Ce; wherein 0 <x<1,0.5≤y≤0.6,0<δ<1。 6. The method for preparing a lithium ion positive electrode material according to claim 4, characterized in that: In step 2, the mass ratio of the silicate high entropy amorphous material to the conventional positive electrode material is 0.1% to 10%:

1.

7. The method for preparing a lithium ion positive electrode material according to claim 4, characterized in that: In step 2, the ball milling mixing time ranges from 1 to 8 hours, and the ball milling mixing speed ranges from 300 to 1000 rpm.

8. The method for preparing a lithium ion positive electrode material according to claim 4, characterized in that: In step 3, the sintering temperature is 400-800° C. and the sintering time is 2-6 hours.

9. A lithium ion battery, characterized in that: The lithium-ion battery consists of a lithium-ion positive electrode coated and modified by an amorphous oxide, a lithium negative electrode and an electrolyte, wherein the lithium-ion positive electrode coated and modified by an amorphous oxide is prepared based on the lithium-ion positive electrode material prepared by the lithium-ion positive electrode material preparation method according to claims 1-3.

10. A method for preparing a lithium ion battery, characterized in that: The following steps are involved: Step S1. Mixing the lithium ion positive electrode material prepared by the method for preparing the lithium ion positive electrode material according to claims 1-3 with conductive graphite, PVDF binder and N-methylpyrrolidone in a certain mass ratio; Step S2. After mixing, all the raw materials are uniformly mixed by mechanical homogenization, and the homogenization time ranges from 60 to 120 minutes; Step S3. coating the mixed slurry on the copper foil with a coating thickness of 50-150 μm; Step S4. Bake the coated copper foil at a certain temperature for 6 to 12 hours to remove the NMP solvent; Step S5. Place the dried electrode obtained in step 4 in a vacuum oven and bake for 6 to 12 hours to remove moisture adsorbed by the electrode; Step S6. After obtaining the electrode sheet, cut it into positive electrode sheets of a certain diameter; Step S7. Assemble the positive electrode sheet, electrolyte and metal lithium sheet to obtain the desired lithium-ion battery.

Citation Information

Patent Citations

  • Delocalized anions for use as electrolytic solutes

    CA2194127A1

  • Surface coating modified lithium ion battery positive electrode material as well as preparation method and application thereof

    CN113921773A

  • Polysilicate coated and modified ternary sodium electric precursor and preparation method thereof

    CN116239160A

  • High-entropy disilicate nanoparticle / amorphous silicon dioxide and silicon carbide nanowire composite aerogel as well as preparation method and application thereof

    CN116789442A

  • High-entropy oxide solid-state coated positive electrode material as well as preparation method and application thereof

    CN118545773A

Cited By

  • Lithium cobalt oxide positive electrode material preparation method, positive electrode material, positive electrode plate and battery

    CN121317899A